Pengaruh Disiplin Kerja, Motivasi Kerja, dan Loyalitas Terhadap Kinerja Karyawan PT Multi Karya Bajatama di Kota Batam - Edison Edison; Alice Erni Husein (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of work discipline, work motivation, and loyalty on employee performance at PT Multi Karya Bajatama in Batam City using a descriptive quantitative approach. The study population consisted of 102 employees, with a sample of 81 respondents determined using the Slovin formula and simple random sampling techniques. Data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results of the multiple linear regression analysis indicate that work discipline has a positive and significant effect on employee performance with a contribution of 24.3%, work motivation also has a significant effect with a contribution of 27.0%, while loyalty has the most dominant influence of 35.1%. The coefficient of determination (R2) analysis confirms that overall, these three variables influence employee performance with a contribution value of 71.1%. Therefore, it can be concluded that improving employee performance is strongly influenced by the implementation of good work discipline, increased motivation, and strengthening employee loyalty on an ongoing basis. Statistical testing through t-tests and F-tests confirms that work discipline, work motivation, and loyalty have a positive and significant effect on employee performance, both individually and collectively.